A dog's journey [videorecording (DVD)] - Mancuso, Gail, 1958-; Quaid, Dennis; Helgenberger, Marg; Cameron, W. Bruce (Universal Pictures Home Entertainment, 2019)
Over several lifetimes, a dog discovers that he must protect Ethan's granddaughter.